2009
DOI: 10.1007/s11248-008-9240-1
|View full text |Cite
|
Sign up to set email alerts
|

Different subcellular localization and glycosylation for a functional antibody expressed in Nicotiana tabacum plants and suspension cells

Abstract: Genes encoding the heavy and light chains of LO-BM2, a therapeutic IgG antibody, were assembled in the tandem or inverted convergent orientation and expressed in Nicotiana tabacum plants and BY-2 suspension cells. The tandem construct allowed higher expression in both expression systems. A similar degradation pattern was observed for the secreted antibody recovered from the leaf intercellular fluid and BY-2 culture medium. Degradation increased with leaf age or culture time. Antibodies purified from leaf tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 43 publications
(79 reference statements)
0
80
1
Order By: Relevance
“…Western blot analysis of the HC in the extracts showed the presence of two bands at about 35 and 20 kDa indicating specific protein degradation. The 35 kDa band was already described in literature for mAbs expressed in suspension cultures (De Muynck et al 2009;Fischer et al 1999) and corresponded to a carboxy terminal protein fragment. These observations are in accordance with our previous work in which we demonstrated that mAb H10 is proteolytically cleaved to form functional Fab fragments, indicating that a specific degradation of the antibody HC occurred around the hinge region (Villani et al 2009).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Western blot analysis of the HC in the extracts showed the presence of two bands at about 35 and 20 kDa indicating specific protein degradation. The 35 kDa band was already described in literature for mAbs expressed in suspension cultures (De Muynck et al 2009;Fischer et al 1999) and corresponded to a carboxy terminal protein fragment. These observations are in accordance with our previous work in which we demonstrated that mAb H10 is proteolytically cleaved to form functional Fab fragments, indicating that a specific degradation of the antibody HC occurred around the hinge region (Villani et al 2009).…”
Section: Discussionmentioning
confidence: 63%
“…The 35 and 20 kDa bands perfectly matched those previously described in the western blot analysis of total fresh leaf extract. It must be noted, that both the 35 and 12 kDa bands were already evidenced in the IFs of tobacco leaves expressing the LO-BM2 mAb (De Muynck et al 2009). This higher antibody degradation observed in the IFs was likely due to the presence of specific peptidases in the apoplast as previously demonstrated both in N. benthamiana and N. tabacum (Delannoy et al 2008;De Muynck et al 2009;Drake et al 2009).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…VENUS is a yellow fluorescent protein gene and was amplified from the plasmid pVenus-N1-NPY (Nagai et al 2002) by PCR using the primers VENUS5 (5 0 -ggcggagctggtggagctggtctcgagatggtgagc aagggcgag-3 0 , XhoI site underlined) and VENUS3 (5 0 -ataaggatccttacttgtacagctcgtc-3 0 , BamHI site underlined). The GUS and VENUS sequences were then fused by splice overlap extension and introduced as a KpnI/BamHI fragment into the multi-cloning site of pAUX3131-En2pPMA4-[KpnI-ScaI-XhoI-BamHI-SmaISacI]-tNOS (De Muynck et al 2009) to create the pAUX3131-En2pPMA4-GusVenus-tNOS plasmid.…”
Section: Construction Of the Hsp3-gusvenus (Gv) Expression Vectormentioning
confidence: 99%
“…The gel was washed 3 9 20 min at room temperature in 2.5% Triton X-100 then incubated for 16 h at 37°C in buffer [10 mM MES pH5.5 (KOH), 5 mM CaCl 2 , 1% Triton X-100], and stained by Coomassie brilliant blue R250 (De Muynck et al 2009). …”
Section: Zymographymentioning
confidence: 99%